Analysis Of Organizational Culture Using Ocai Method At PT Graha Manggala Abadi Makassar Company - Agustinus Leta Napu; Imanuel Wellem; Emilianus Eo Kutu Goo (Harmoni Economics: International Journal of Economics and Accounting, 2025)
Higher education is an important level of education in preparing students for the world of work. One of the programs that supports the development of student competencies is the internship program, which provides opportunities for students to develop soft skills and adapt to the work environment. This study aims to determine the profile of organizational culture at PT. Graha Manggala Abadi Hotel Harper Perintis By Aston Makassar at present and expected in the future based on employee perceptions. based on six main dimensions: dominant characteristics, leadership This study uses qualitative research by analyzing organizational culture at PT. Graha Manggala Abadi Hotel Harper Perintis By Aston Makassar organization, employee management, organizational glue, strategic emphasis, and success criteria. Data were collected through questionnaires that were distributed and analyzed using the Organization Culture Assessment Instrument (OCAI) analysis. Based on the results of the OCAI analysis for all dimensions of organizational culture, it shows an increase in Clan Culture and Adhocracy Culture. In the organizational aspect, efforts are needed to maintain a balance between renewal, efficiency, and cohesion by strengthening the values ​​of Clan Culture and adopting innovative elements from Adhocracy Culture.